Floristic and phytosociological aspects of a deciduous forest in the region of the Upper Uruguay -RS - Georgin, Jordana; Eloy, Jean Brun; Oliveira, Gislayne Alves; Rosa, Ana Lúcia Denardin da; Lazzari, Laudison (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This study aimed to characterize the floristic and phytosociological aspects of a Deciduous Forest in the region of Alto Uruguay -RS. For that were installed randomly in the study area, 15 sample units of dimensions 10 x 10 m (100 m²), totaling 1500 sq sampled. In these individuals were all raised to the height of the largest circumference of the chest or equal to 15 cm, each being identified at the level of genus and species family. The horizontal structure of the fragment was characterized by phytossociological parameters (density, dominance, frequency and importance value) and diameter distribution, the vertical structure was carried out by division into five strata of different sociological positions. According to the results, Fabaceae and Meliaceae were the families that stood out in number of genera, species and individuals. Gymnanthesconcolor, Soroceabonplandii and Eugenia schuechiana were the most important species of the forest. This, in general, shows the diameter distribution in the form of inverted "J", with the vast majority of individuals is focused on sociological Dominated position.